Triatomine Epidemiology in the Province of Río Negro (Veterinary Science, 2021)
Chagas is an endemic epidemic disease of vector transmission in the Province of Rio Negro caused by Trypanosoma cruzi, transmitted by triatomines. The Chagas control program in the province of Rio Negro certified, through serological and entomological indicators, the interruption of vector transmission throughout the province. However, in recent years, conditions have been generated that may allow the re-emergence of the disease, such as the eventual domiciliation of wild vinchucas such as T patagonico. The objective was to evaluate the epidemiological situation of the vector through studies of home and peri-home infestation by triatomines and to carry out resistance analyzes to insecticides that were applied for many years in control. As a result, 143 homes were evaluated and 66 light traps were placed. In the intra-domicile all the dwellings were negative, with 3 being positive in the peri-domicile (2.1%) with captures of T-infestans and T. patagonica. No triatomines were captured with the light traps. The captured triatomines were T. infestans and T. patagonica, which were all negative for T. cruzi. Insecticide resistance studies showed that the colonies are still susceptible to deltamethrin.colonies are still susceptible to deltamethrin.
Keywords: Chagas disease, triatoma, epidemiology, control